(untitled) (THE ACADEMIA, 2026)
State and media in Nepal often criminalize squatters portraying them as city pollutes, encroachers, threats to public law and order, while their contribution is completely forgotten. This research investigates how the squatters in Kathmandu are criminalized and how they resist this by constructing counter-narratives. Using the ethnographic field work held between January and July 2025 deeply engaging with community leaders, NGOs activists, cooperatives activists and residents, the study demonstrates that state criminalizes squatters for occupation of the public land without consent, thus enforcing them to evict the settlement while the squatters challenges such state narratives claiming that they have protected land from the encroachment of private builders and contributed to launch development activities. These counter-narratives are produced and reproduced through tactful engagement with parties, legal mobilization, and partnership with NGO. The findings explores that criminalization works as tool to drive eviction attempts to destroy the settlement while counter-narratives serve developing political agency and collective mobilization.